Laser treatment of benign prostatic obstruction: basics and physical differences - Bach, Thorsten; Rassweiler, Jens (European urology, 2012)
Context Laser treatment of benign prostatic obstruction (BPO) has become more prevalent in recent years. Although multiple surgical approaches exist, there is confusion about laser-tissue interaction, especially in terms of physical aspects and with respect to the optimal treatment modality. Objective To compare available laser systems with respect to physical fundamentals and to discuss the similarities and differences among introduced laser devices. Evidence acquisition The paper is based on the second expert meeting on the laser treatment of BPO organised by the European Association of Urology Section of Uro-Technology. A systematic literature search was also carried out to cover the topic of laser treatment of BPO extensively. Evidence synthesis The principles of generation of laser radiation, laser fibre construction, the types of energy emission, and laser-tissue interaction are discussed in detail for the laser systems used in the treatment of BPO. The most relevant laser systems are compared and their physical properties discussed in depth. Conclusions Laser treatment of BPO is gaining widespread acceptance. Detailed knowledge of the physical principles allows the surgeon to discriminate between available laser systems and their possible pitfalls to guarantee high safety levels for the patient.